SUNNI DAN SYI’AH DALAM HARMONI (Pemikiran M. Quraish Shihab dalam Upaya Rekonsiliasi Ummat) - Ahmad Soleh Sakni (JIA (Jurnal Ilmu Agama), 2018)
The conflict between Sunnis and Shia is not a new problem in the long history of moslem. It is not only focused on the issue of aqidah and worship, but also led to anarchic actions such as those that occur in many places, one of which is Indonesia such as in Madura. M. Quraish Shihab (MQS) Indonesian Muslim scholar, through his endeavor, tried to ensure that these two schools could join hands in living a life shaded by Islamic teachings. MQS tries to unite and make harmony between the two by prioritizing aspects of the similarities between the two streams, not sharpening differences. This was confirmed by M. Quraish Shihab in an expression related to disputes between the two groups, "We are brothers, we do not need to be tense with each other. Heaven is too wide so there is no need to monopolize heaven just for ourselves. So do not insult each other." Quraish Shihab statement has made people accuse him of being a defender of Shi'ism, even of being Shi'ites, but on several occasions he stated that he did not adhere to Shi'ism, he only tried to find the right solution in dealing with differences in understanding and ideology between Sunnis and Shiites.